Pressurized organic electrodes enable practical and extreme batteries - Zhixiao Xu; Yunkai Xu; Yunkun Qiu; Yan Cao; Sergey Gasilov; Ge Li; Jun Lu; Xiaolei Wang (Nature Communications)
Abstract While organic batteries hold promise for sustainable energy storage, a considerable gap persists between research and application concerning testing conditions and cell cost. Here, we report pressurized organic electrodes tailored for practical applications. Outperforming prior organic electrodes, pressurized organic electrodes excel under challenging/extreme condition including high mass loadings (50–150 mg cm−2), active material fraction (up to 95%), low N/P ratio (0.8–2), and lean electrolyte, delivering high areal/volumetric capacity in full cells. Moreover, pressurized organic electrodes exhibit broad applicability, thriving in diverse battery systems (Li+/NH4 +/H+/Na+/Zn2+/Mg2+ ion batteries) and organic materials (molecule, polymer, salt), consistently demonstrating enhanced performance compared with unpressurized ones. The improved capacity, rate, and cycling performance of pressurized electrodes result from pressure-induced structural and property changes in organics including crystal orientation, enhanced π-π interaction, favorable electrode porosity/tortuosity, accelerated chemical reactivity, and boosted electronic conductivity. Along with simple, efficient, green, and cost-effective manufacturing features, pressurized organic electrodes offer a promising route towards organic battery application.